2012
DOI: 10.1126/scitranslmed.3003377
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Prediction of Drug Effects and Interactions

Abstract: Adverse drug events remain a leading cause of morbidity and mortality around the world. Many adverse events are not detected during clinical trials before a drug receives approval for use in the clinic. Fortunately, as part of postmarketing surveillance, regulatory agencies and other institutions maintain large collections of adverse event reports, and these databases present an opportunity to study drug effects from patient population data. However, confounding factors such as concomitant medications, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
660
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 701 publications
(666 citation statements)
references
References 39 publications
4
660
0
2
Order By: Relevance
“…Now consider the challenge of evaluating signal detection performance against broad references of such positive and negative controls. Contemporary research has reported improved performance of multivariate analytics compared to disproportionality screening, for the analysis of individual case reports [6,8]. This seems plausible, since the new methods offer innovations such as adjustment for comedications and indications for treatment.…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Now consider the challenge of evaluating signal detection performance against broad references of such positive and negative controls. Contemporary research has reported improved performance of multivariate analytics compared to disproportionality screening, for the analysis of individual case reports [6,8]. This seems plausible, since the new methods offer innovations such as adjustment for comedications and indications for treatment.…”
Section: Examplesmentioning
confidence: 99%
“…There are individual case reports [1], longitudinal health records [2], internet search patterns [3] and social media [4]. There is disproportionality analysis [1], regression [5,6], adjustment by propensity scores [7,8], self-controlled designs [2,9] and more. Expert judgment is important in choosing methods and datasets for pharmacovigilance, but ideally we would like to see objective evidence that a chosen approach can be expected to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…It also retrieves the information from the spontaneous reporting systems such as US Food and Drug Administration's Adverse Event Reporting System (AERS) [2][11] [13] by using the technologies like the semantic web [15] and linked data.…”
Section: Knowledge Based Approachesmentioning
confidence: 99%
“…The paper also notes that there are inconsistencies in the severity grading system between the compendia. Tatonetti et al [7] present the Offsides database for drug effects and the Twosides database for drug-drug interaction side effects, and use these databases to attempt to identify drug targets, predict drug indications and discover drug class interactions. Shah et al [8] finds that the drug-drug interaction knowledge databases used for clinical decision support systems are not consistent with official package labels, causing spurious warnings and inaccurate information.…”
Section: Introductionmentioning
confidence: 99%